Post-harvest losses in potato in Nyandarua County - Scollard, Phoebe; Hoffmann, Vivian; Kago, Kennedy; Parker, Monica (International Food Policy Research Institute, 2022)
Irish potato is the second most important food crop in Kenya after maize (Kaguongo et al., 2014). Potato production in Kenya is expected to grow, as farmers are being encouraged both by climate shifts and by the government to diversify their production from reliance on maize. Many farmers are opting to grow potato because it is fast-maturing compared to maize and can be used to bridge the gap during shortages of the staple grain (ibid). However, significant barriers exist to more productive and profitable potato cultivation in East Africa, including low quality of seed potato, poor disease and soil fertility management, and high rates of post-harvest losses (Schulte-Geldermann, 2013). Average potato yields in Nyandarua County are 3-4 tonnes per acre per season, well below the 10 tonnes per hectare that can be realised by professional farmers using certified seed and sound agricultural practices (Kaguongo et al., 2014).